ANALISIS PEMBELAJARAN IPAS MI TERKAIT MEDIA PEMBELAJARAN : STUDY KASUS - Iqbal Miftakhul Mujtahid; Nabiha; Rian Vebrianto; Adisti Yuliastrin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Theoretically sound educational ideas and media for teaching are often easier to discuss and debate than their practical implementation in the classroom. Consequently, the purpose of this research is to find problems with the use of learning theories and pedagogical tools. In order to provide a thorough analysis, this research uses a mixed-methods case study methodology, which combines quantitative data with qualitative results. Two science instructors and twenty-six third graders from an elementary school participated in the research. After gathering data via surveys, in-depth interviews, and observational studies, the researchers examined the quantitative data using descriptive statistics and the qualitative findings using thematic analysis. Using visual aids like photos and videos helps 73% of students understand the topic better, while narrative-based learning engages 65% of students. Students' inability to conceptualize abstract ideas is exacerbated by an over-reliance on textbooks, according to field observations, which in turn causes extreme boredom and disengagement. So, it's safe to say that the absence of visual and narrative components is the biggest problem with IPAS lessons. In order to improve students' motivation and critical thinking abilities in the digital age, this research suggests integrating digital storytelling technology with interactive visual media.